Evaluation of battery performance for solar mobile phone charger for rural dweller usage - Emetere Moses E.; Akuwudike E.C.; Afolalu Sunday A. (E3S Web of Conferences, 2023)
This research is an initiative to improve the standard of living of rural dwellers and deprived settlements in a semi-urban location where epileptic power supply is predominant. The study is aimed at evaluating battery performance for the construction of a solar-powered mobile charger aimed at improving a steady power supply for electronic devices (phones, tablets, etc.), given the high and increased dependence on such devices in recent times. The solar-powered mobile charger was tested using various batteries available in the Nigerian market to determine the cheapest and most effective device to help rural dwellers. The constructed device was tested via its output voltage, current, time, and temperature. The results were subjected to further analysis by using Matlab and PVeducaction software for presentation and interpretation. The results of the analysis showed an efficiency value of seventy percent (70%) and a standard nominal voltage reading between 3.7 and 4.2 volts (V). The performance of the four batteries used affirmed its basic findings, however, Nickel-Metal Hydride (Ni-MH) batteries and Lithium-ion (Li-ion) metal (Ni-MH) batteries showed stability among the batterires used. The study recommends the commercialization phase of the construction to improve the living standards of rural dwellers and deprived settlements in a semi-urban location.